Pop Theory: The Architecture of Late Night Shopping. Issue 3 (2nd September 2017) - Runting, Helen; Sjögrim, Rutger; Torisson, Fredrik
Abstract: Inviting audiences into the late-night, precarious world of (photo)shopping, we explore the way in which the ghostly figures of the Photoshop world – its exhausted architects, indebted consumers, and the two-dimensional cut-outs that populate its spaces – are all put to use in a project of producing subjectivities through environments. Feminist critiques of visuality provide a basis in understanding the play between bodies and worlds that set this production in motion. By looking at the mechanics of "pre-occupation" that allow us to inhabit such images, we speculate: could a re-theorization of this most commercial of "extra-architectural services" (visualization) allow the activity of shopping be put to more radical use?